Crustal-scale duplexing beneath the Yarlung Zangbo suture in the western Himalaya - Gao, Rui; Lu, Zhanwu; Klemperer, Simon L.; Wang, Haiyan; Dong, Shuwen; Li, Wenhui; Li, Hongqiang (Nature geoscience, 2016)
The fate of the Indian plate during continental collision with Asian terranes, and the proportion of the Indian crust that is underthrust or subducted beneath Tibet as opposed to transferred to the upper (Himalayan) plate, are much debated. The active geometry of low-angle underthrusting or subduction of the Indian plate beneath the Lesser and Greater Himalayan thrust sheets is well known from seismic imaging. Previously, only lower-resolution images of the Main Himalayan Thrust have been obtained beneath the Yarlung Zangbo suture that separates Indian and Asian rocks at the surface. It remains controversial whether the orogenic wedge between the Main Himalayan Thrust and the Yarlung Zangbo suture, formed of Indian crust transferred to the upper plate, is evolving by thrust-faulting in a critical-taper wedge or by southward extrusion of a ductile channel flow. Here we present a seismic reflection profile across the western Himalaya at 81.5° E, and show that the Main Himalayan Thrust dips ∼20° to ∼60 km depth beneath the Yarlung Zangbo suture, approaching a continuous Moho reflection at ∼70–75 km depth. The Indian crust being transported northwards beyond the Yarlung Zangbo suture is no more than ∼15 km thick, reduced from its original ∼40 km thickness by transfer of material from the lower plate to the upper plate through crustal-scale duplexing. The fate of the Indian plate during collision with Asia is debated. Seismic images of the western Himalaya reveal large-scale thrust faults that transfer Indian crust upwards, into the overriding Asian plate.